Translation analysis of figurative language contained in sentences in The Fault in Our Stars - Magistradewi Ayu Paramitha; Nur Saptaningsih (Jurnal Linguistik Terapan, 2019)
This research was conducted to analyze the translation of figurative language contained in sentences in a novel entitled The Fault in Our Stars. The data are categorized into two: the linguistic data and translation data. Linguistic data refer to the figurative language. Translation data refer to the techniques used and the translation quality assessment. The result shows that there are 96 data which contain figurative language and 13 techniques used. The most dominant technique used is established equivalent, followed by the technique of variation. Both of the techniques above mostly reflect good quality of translation, while the other techniques such as amplification, reduction, modulation, borrowing, compensation, discursive creation, adaptation, generalization, transposition, literal translation, and particularization reflect both quite good and bad qualities of translation. The total score of the translation quality is 2.97. It is categorized as high-quality translation.